Christopher Van Deventer papers - Van Deventer, Christopher, -1838.
Correspondence, list of noncommissioned U.S. army officers confined to Quebec during the War of 1812, and newspaper clipping. Correspondents include John Armstrong, John C. Calhoun, Samuel Cooper, Gideon Davis, William Hoinder, John Eatton Le Conte, Morgan Lewis, James Monroe, Winfield Scott, and Henry Wheaton.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Armstrong, John, -- 1758-1843 -- Correspondence; Calhoun, John C. -- 1782-1850 -- Correspondence; Cooper, Samuel, -- 1798-1876 -- Correspondence; Davis, Gideon -- Correspondence; Hoinder, William -- Correspondence; Le Conte, John Eatton, -- 1784-1860 -- Correspondence; Lewis, Morgan, -- 1754-1844 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Scott, Winfield, -- 1786-1866 -- Correspondence; Wheaton, Henry, -- 1785-1848 -- Correspondence; United States -- Army -- History -- War of 1812.; Quebec (Province) -- History, Military; United States -- History -- War of 1812 -- Prisoners and prisons, British; Army officers